Linking migration and parent academic involvement: evidence from Angola - Vaz, Sara (2018)
This study examines the effect of past migration experience on the multiple facets of parent involvement. We run OLS and two-stage least squares regressions on a representative sample of catholic schools in the city of Luanda, Angola. Our results do not suggest a different level of academic involvement by returned migrants. We find, however, that parent level of education, wealth, family composition and school performance are strong predictors of parent involvement. In addition, we find evidence of a quadratic relation of age with most of the dimensions of parent involvement. Gender wise, we show that mothers are significantly more involved with their children in relation to fathers, and that parent involvement is not conditional on child gender, suggesting the nonexistence of a child gender bias.